Transformable self-assembling peptide nanoplatforms with tumor microenvironment responsiveness for tumor stem cell suppression and immunomodulation - Chen Wei; Xinyu Sun; Lijuan Gao; Yue Wang; Fantao Lin; Yao Du; Xiaoyu Zhao; Wei Gao; Jingkun Bai (Materials Today Bio, 2025)
Breast cancer stem cells (BCSCs) drive tumor formation and growth via self-renewal, differentiation, and high tumorigenic potential, and the persistence of BCSCs is an important cause of treatment failure in patients with breast cancer. In addition, the tumor microenvironment promotes the maintenance of BCSC stemness, inhibits immune cell activity, and forms an immune escape “barrier”. In this study, we developed an amphiphilic peptide nanocarrier system, PA/Pep1, with an RGD-targeting sequence. The delivery system simultaneously encapsulates the hydrophobic drugs paclitaxel (PTX) and all-trans retinoic acid (ATRA) and releases them in response to low pH in the tumor microenvironment. PA/Pep1 causes apoptosis in breast cancer cells, induces the differentiation of BCSCs and inhibits their expression, thus enhancing the killing effect of PTX. In breast cancer, PA/Pep1 effectively alleviates immune evasion by modulating transforming growth factor-β (TGF-β) and interleukin-6 (IL-6), thereby reducing the expression of programmed cell death-ligand 1 (PD-L1). Importantly, the transformation of the nanosystems into forms with high aspect ratios under acidic conditions effectively reduced drug efflux and extended the duration of drug action. In conclusion, the combination of stem cell therapy and immunotherapy, as well as the development of novel deformable amphiphilic peptide nanocarrier systems, provides new possibilities for breast cancer treatment.